INTEGRASI PRINSIP SUSTAINABLE DEVELOPMENT GOALS (SDGs) DALAM KEBIJAKAN SEKOLAH: MEWUJUDKAN PENDIDIKAN RAMAH ANAK, GENDER, DAN DISABILITAS - Sukandar; Eko Handoyo, Fathur Rokhman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Child-Friendly Schools (SRAs) are educational concepts that aim to create a safe, comfortable, and inclusive learning environment, with a focus on children's physical, emotional, social, and psychological well-being. The implementation of SRA in Indonesia refers to the regulations in the Child Protection Law and the Regulation of the Minister of Education and Culture. Its main objective is to provide access to education for all children, including vulnerable groups, free from violence and discrimination. However, the implementation of SRA in Indonesia is still faced with obstacles such as limited teacher training and adequate facilities, especially in rural areas. In addition, gender mainstreaming and women-friendly education are important factors to achieve gender equality in education, with a focus on eliminating gender-based discrimination and women's empowerment. In the context of disability, inclusive education also faces major challenges, although supportive regulations already exist. There are still obstacles related to the lack of disability-friendly facilities and teacher training. Achieving optimal inclusive education requires collaboration between the government, schools, communities, and families. Social awareness and improved facilities and teacher training are the keys to the successful implementation of SRA and inclusive education in Indonesia.